Pembaharuan Model Penilaian Pembinaan Narapidana Residivis Berbasis Teknologi - Darmawati Darmawati (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2022)
The purpose of this study is to create a technology-based assessment model for special coaching recidivists by setting indicators of achievement of the implementation of activities so that the implementation of coaching can run well and directed. The type of research used in this study is a combination of normative legal research and empirical legal research. The implementation of the development of recidivist prisoners is not fully in line with the meaning of rehabilitation because there are still recidivist prisoners who repeat their crimes. The assessment model for fostering recidivist prisoners is made according to the type of crime committed and indicators of achievement of the assessment are set and the assessment system must be supported by online-based technology so that coaching can be controlled and is more transparent.